Al-Qalaq fī Ḍaw’ al-Qur’ān al-Karīm wa ‘Ilm al-Nafs al-Ḥadīth - Al-Shwike, Nadia; Sabbah, Suheir Sulieman (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
The study aimed to explore anxiety as a psychological phenomenon, including its types, causes, and treatment methods in light of the Holy Quran and modern psychology. The research employed a descriptive-analytical approach by collecting relevant Quranic verses and comparing these concepts with those found in psychology books, as well as examining the insights of Muslim scholars and modern psychology regarding anxiety, its types, causes, and treatment. The study found that anxiety is a modern psychological concept that affects individuals due to fear, stress, or excessive thinking about certain life issues, often of unknown origin, and is a source of psychological pressure. It also revealed that the verses in the Quran addressing doubt and suspicion refer to anxiety in its modern sense. Additionally, the study showed that Quranic stories illustrate the levels and types of anxiety experienced by the prophets in different situations, including psychological anxiety, social anxiety, and objective anxiety related to their prophetic missions. Furthermore, the Quranic verses focused on the anxiety of specific groups, such as hypocrites and disbelievers, particularly concerning their doubt and suspicion in receiving the divine message and opposing the prophets. The study recommends incorporating psychological studies rooted in Islamic heritage into university curricula and encourages researchers to conduct in-depth studies on such topics. It also advocates for integrating psychological studies from the Quran and Sunnah with modern psychology.